Assessing relative potential economic impacts of an oil spill on commercial fisheries in the Great Australian Bight using a Bayesian Belief Network framework. (November 2018) - Pascoe, Sean
Abstract: Review based experiences of oil-spill induced impacts on fisheries were used to develop a Bayesian Belief Network (BBN) to evaluate the potential economic consequences of a (hypothetical) oil spill in the Great Australian Bight, an area currently being explored by several major international oil companies. The model differs from most previous BBN analyses in that it also considers the relatively short term economic impacts of such a spill, encompassing market and fisher behaviour, as well as impacts on the stocks affected directly by the spill. The results suggest that impacts vary depending on the characteristics of the fishery (i.e. main species, location etc.) and the timing and extent of the oil spill, but market, management and fisher behavioural responses (and their ability to respond) were found to have the greatest impact on the final economic outcomes.